Vlog (Video Blogging) Kelestarian Lingkungan Sungai Sebagai Media Pembelajaran Tematik Untuk Siswa Sekolah Dasar - Ilma, Rahmatika Dwi; Juhadi, Juhadi (Edu Geography, 2020)
The purpose of this study was (1) design a prototype design and creating a vlog learning media for thesustainability of the river environment. (2) knowing the feasibility of vlog learning media about the sustainabilityof the river environment for elementary school students. (3) knowing the level of students' knowledge of thesustainability of the river environment. The research method used was pre-experimental with a one-shoot casestudy design. The population in this study were all 5th grade students of elementary school in Ujungbatu Village,Jepara District, Jepara Regency. The sample technique used is a saturated sample. Data collection techniquesusing observation, interviews, questionnaires, and tests. The data analysis technique used is descriptive statistics.The results of the vlog learning media validation by the first validator showed that it was feasible with a score of30, while the second validator showed that it was very feasible with a score of 39. After the vlog was declaredappropriate for learning media, researchers displayed vlogs for elementary school students. Obtained results inSD N 2 Ujungbatu 47.1% of students have very good knowledge, 5.8% of students have less knowledge whereas,in SD N 3 Ujungbatu, 32.3% of students have very good knowledge and 3.2% students have less or no goodknowledge about the sustainability of the river environment. Tujuan penelitian ini adalah (1) Merancang desain prototipe dan membuat media pembelajaran vlogkelestarian lingkungan sungai. (2) Mengetahui kelayakan media pembelajaran vlog tentangkelestarian lingkungan sungai untuk siswa sekolah dasar. (3) Mengetahui tingkat pengetahuan siswaterhadap kelestarian lingkungan sungai. Metode penelitian yang digunakan adalah pre-experimentaldengan desain one-shoot case study. Populasi dalam penelitian ini adalah seluruh siswa kelas 5 sekolahdasar di Desa Ujungbatu, Kecamatan Jepara, Kabupaten Jepara. Teknik sampel yang digunakanadalah sampel jenuh. Teknik pengambilan data menggunakan observasi, wawancara, angket, dantes. Teknik analisis data yang digunakan yaitu statistik deskriptif. Hasil validasi media pembelajaranvlog oleh validator pertama menunjukkan layak dengan jumlah skor 30, sedangkan validator keduamenunjukkan sangat layak dengan jumlah skor 39. Setelah vlog dinyatakan layak digunakan untukmedia pembelajaran, peneliti menayangkan vlog pada siswa sekolah dasar. Diperoleh hasil pada SDN 2 Ujungbatu 47,1% siswa mempunyai pengetahuan yang sangat baik, 5,8% siswa mempunyaipengetahuan yang kurang sedangkan, pada SD N 3 Ujungbatu, 32,3% siswa mempunyaipengetahuan yang sangat baik dan 3,2% siswa mempunyai pengetahuan yang kurang atau tidak baikterhadap kelestarian lingkungan sungai.